Adipose-derived stem cell exosomes regulate Nrf2/Keap1 in diabetic nephropathy by targeting FAM129B - Peiyao Ren; Fengmei Qian; Lanjun Fu; Wenfang He; Qiang He; Juan Jin; Danna Zheng (Diabetology & Metabolic Syndrome, 2023)
Abstract Background Exosomes from adipose-derived stem cells (ADSCs-Exos) have exhibited a therapeutic role in diabetic nephropathy (DN). Further studies are needed to investigate how ADSCs-Exos regulate oxidative stress and inflammation in high glucose-induced podocyte injury. Methods An enzyme-linked immunosorbent assay (ELISA) was used to detect cellular inflammation. Reactive oxygen species (ROS) levels were assessed using flow cytometry in podocytes with different treatments. A malondialdehyde (MDA) kit was used to evaluate the lipid peroxidation levels in podocytes and kidney tissues of mice. Western blotting and co-immunoprecipitation were performed to detect protein expression and protein-protein interactions. Results ADSCs-Exos reversed oxidative stress and inflammation in podocytes and kidney tissues of DN mice induced by high glucose levels in vitro and in vivo. Interference with heme oxygenase-1 expression could reverse the improvement effect of ADSCs-Exos on oxidative stress induced by high glucose levels. Furthermore, high glucose inhibited nuclear factor erythroid 2-related factor 2 (Nrf2) protein expression and promoted Kelch-like ECH-associated protein 1 (Keap1) protein expression in podocytes, as well as their binding ability. As a potential target for Nrf2/Keap1 pathway regulation, FAM129B expression in podocytes is regulated by high glucose and ADSCs-Exos. Moreover, FAM129B siRNA blocked the inhibitory effect of ADSCs-Exos on intracellular ROS and MDA upregulation induced by high glucose in podocytes. Conclusion ADSCs-Exos regulate the Nrf2/Keap1 pathway to alleviate inflammation and oxidative stress in DN by targeting FAM129B, which may provide a potential therapeutic strategy for DN.